2014
DOI: 10.1080/10810730.2014.936568
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Health Insurance Literacy Measure (HILM): Conceptualizing and Measuring Consumer Ability to Choose and Use Private Health Insurance

Abstract: Understanding health insurance is central to affording and accessing health care in the United States. Efforts to support consumers in making wise purchasing decisions and using health insurance to their advantage would benefit from the development of a valid and reliable measure to assess health insurance literacy. This article reports on the development of the Health Insurance Literacy Measure (HILM), a self-assessment measure of consumers' ability to select and use private health insurance. The authors deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
178
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(189 citation statements)
references
References 10 publications
5
178
0
6
Order By: Relevance
“…Most American adults (75 %) were moderately or very confident they knew how to use health insurance, yet when presented with a cost-sharing scenario only 20 % could estimate the correct cost of a doctor's visit (Paez et al 2014). The study also found that less than half (42 %) of those surveyed were unlikely or somewhat likely to find out what their health plan covered before they went for health care services (Paez et al 2014). To reduce the complexity and suboptimal decision-making, consumers prefer fewer options and information that is presented in a single or simplified format (Hibbard et al 2002;Loewenstein et al 2013).…”
Section: American's Lack Of Health Insurance Literacymentioning
confidence: 99%
See 4 more Smart Citations
“…Most American adults (75 %) were moderately or very confident they knew how to use health insurance, yet when presented with a cost-sharing scenario only 20 % could estimate the correct cost of a doctor's visit (Paez et al 2014). The study also found that less than half (42 %) of those surveyed were unlikely or somewhat likely to find out what their health plan covered before they went for health care services (Paez et al 2014). To reduce the complexity and suboptimal decision-making, consumers prefer fewer options and information that is presented in a single or simplified format (Hibbard et al 2002;Loewenstein et al 2013).…”
Section: American's Lack Of Health Insurance Literacymentioning
confidence: 99%
“…The ACA addressed several factors associated with consumers' abilities to select a health insurance plan and make use of their health insurance benefits; however, during implementation, consumers' health insurance literacy received less attention (Paez et al 2014). For example, some states restricted the number of plans an insurer could offer on the health insurance marketplace to simplify the consumer's health insurance shopping experience (Dash et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations